Building the New Socialist Countryside: Tracking Public Policy and Public Opinion Changes in China. (13th May 2016) - Stepan, Matthias; Han, Enze; Reeskens, Tim
Abstract: Ever since the introduction of the national political programme of "Building a new socialist countryside" (BNSC) in the early 2000s, renewed focus has been cast on how the Chinese government manages the gap between its rural and urban areas in the new millennium. Previous research has mostly studied the social and political consequences of the BNSC initiative without paying particular attention to its effects on public opinion. In this article, we present an analysis of the 2002 and 2008 waves of the mainland China subset of the Asian Barometer. Our results show a significant shift in the perceptions of the rural population in respect to how much impact government policies have on daily life. This shift brings rural perceptions more in line with those of the urban population in 2002. The paper concludes with the implications of our findings for the study of the relations between public opinion and public policy in China. 摘要: 从二十一世纪初开始的建设社会主义新农村运动, 重启了对中国政府新世纪如何处理城乡差距的关注。之前, 对于社会主义新农村建设的研究多聚焦其社会和政治效应, 却从未研究其与公共舆论的关系。在这篇文章里, 我们分析了 2002 年次和 2008 年次关于中国大陆地区的亚洲民主动态调查。我们的研究发现自从建设社会主义新农村运动开始以来, 对于政府政策如何影响日常生活感知的城乡差距有所缩小。我们的结论对于如何研究中国的公共政策和公共舆论提出了一点启发。